2021
DOI: 10.3390/rs13163107
|View full text |Cite
|
Sign up to set email alerts
|

Subsidence Monitoring Base on SBAS-InSAR and Slope Stability Analysis Method for Damage Analysis in Mountainous Mining Subsidence Regions

Abstract: Surface subsidence caused by coal mining has a great impact on the geological and ecological environments and causes damage to houses, roads, and industrial buildings. In order to understand the subsidence pattern in the mountainous mining regions, three mining faces of the Zhangjiamao mining area in the north of Shaanxi province, northwestern China are taken as case study. Firstly, the small baseline subset (SBAS) technology is used to process 12 images obtained in the mining area to investigate the subsidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…PSInSAR is a technique for the modeling and analysis of PS targets based on the stacking of SAR images. The displacement and velocity at each point are calculated using the phase difference between stable targets in the Delaunay network [30][31][32]. For each PS point in the network, the interferometric phase ϕ int includes the topographic (ϕ topo ), noise residual (ϕ noise ), atmospheric delay (ϕ atmo ), and deformation (ϕ de f ) phases; thus,…”
Section: Algorithm For Psinsar Technique Combined With Gnss Pointsmentioning
confidence: 99%
“…PSInSAR is a technique for the modeling and analysis of PS targets based on the stacking of SAR images. The displacement and velocity at each point are calculated using the phase difference between stable targets in the Delaunay network [30][31][32]. For each PS point in the network, the interferometric phase ϕ int includes the topographic (ϕ topo ), noise residual (ϕ noise ), atmospheric delay (ϕ atmo ), and deformation (ϕ de f ) phases; thus,…”
Section: Algorithm For Psinsar Technique Combined With Gnss Pointsmentioning
confidence: 99%
“…The input parameters are described in Table 2. Due to the high temporal and spatial sampling rate, SBAS-InSAR requires few satellite images, but generally, more than eight images, to ensure monitoring accuracy [6,48]. The fast-rate region can be searched for by applying SBAS-InSAR to small SAR data sets, including partial time-series SAR data and new SAR data from strongly developed ground deformation areas.…”
Section: Strongly Developed Moderately Developed Weakly Developedmentioning
confidence: 99%
“…Declercq investigated the post-mining ground deformations and their transition following the closure of coal mines in Belgium by utilizing three decades of MT-InSAR [13]. These studies demonstrated that InSAR techniques can overcome the limitation of point-wise traditional geodetic measurement and are capable of detecting large-scale deformation fields with theoretical accuracy reaching the millimeter level [14].…”
Section: Introductionmentioning
confidence: 99%